COVID-19 DATA ANALYSIS: AN INCENTIVE FOR TOOL DEVELOPMENT WITH ’R’ - Ramos Herrera, Sergio; Carrera Velueta, Jesús Manuel (Kuxulkab’, 2022)
The COVID-19 pandemic has generated a lot of information that has been opened to the general public and to analyze its spatial and temporal evolution, emerging tools have been developed. This work deals with tools such as the ’covid19.analytics’ and ’COVID19’ packages developed with ’R’ statistical software and R-based web applications such as ’COVIDiario’, ’COVID-19 tracker’, among others. These tools visualize the data in regions of interest, facilitating consultation and monitoring by researchers and health authorities. It also shows visualizations of the data in Mexico and Tabasco with the goal of motivating the use of the ’R’ software.